Implementation of Fuzzy Logic in Environmental Control and Disease Diagnosis of Sumatran Fish Puntius tetrazona - Syaqra Nindya Nurafni; Rizqullah Zaky Yudawirja; Joandah Rayla Nabila Annuru; Rakha Akbar Riyanto; Revanda Maulana Zahradiaz; Justin Khaliq Satriadana; Apan Sopian; Nurul Lisnawati; Dzahabiyyah Febrika Zain; Hasna Nursabirah; Mutiara Citra Dewi; Indah Permata Sari Maha; Varel Raihan Rivasa; Hilal Surya Hilmansyah (Batrisya Education, 2025)
Water quality management in rearing media is an important factor to maintain fish health and survival. Optimal water quality can help fish growth and prevent disease. This research aims to develop and implement a Fuzzy Logic-based system to automate water quality management in Sumatran Puntius tetrazona fish aquariums and perform early diagnosis of several diseases that commonly attack Sumatran Puntius tetrazona fish. The use of fuzzy logic using MATLAB is very helpful in monitoring media water quality and fish diseases. This research develops a fuzzy logic-based system to control water quality and diagnose diseases of Sumatran Puntius tetrazona fish. This system uses components such as Arduino IDE, ESP32, dissolved oxygen sensor, temperature sensor, amonia sensor, and pH sensor to collect and process data related to water quality and fish disease diagnosis.